Evaluasi Pemanfaatan E-COMMERCE Jaminan Kesehatan Nasional (JKN) Untuk Meningkatkan Pelayanan di Puskesmas Wonorejo Kota Samarinda - Claudia, Maria Cindi; Nurhasanah Nurhasanah (JURNAL ILMIAH NUSANTARA, 2025)
The utilization of e-commerce platfroms within the National Health Insurance (JKN) system has the potential to enhance healthcare services in primary healthcare centers (Puskesmas). This study aims to evaluate the implementation and impact of e-commerce in the JKN system, focusing on its role in improving efficiency, accessibility, and quality of services at Puskesmas. A mixed-method approach was employed, combining quantative data analysis and quantative interviews with healtcare providers and beneficiaries. The results reveal that integrating e-commerce into the JKN system streamlines administrative processes, facilitates medication procurement, and enhances patient satisfaction. However challenges such as digital literacy gaps and technical limitations remain barriers to optimal utilization. Recommendations for improving e-commerce adoption in the JKN framework include targeted training, infrastructure enchancement, and continous monitoring and evaluation. This evaluation provides valuable insights for policymakers and stakeholders to optimize e-commerce applications in healthcare services delivery.